2008
DOI: 10.1177/1059840511223344
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of School Playground Safety Practices as Reported by School Nurses

Abstract: The purpose of this study was to investigate school playground safety practices. The study used a purposeful sample of school nurses who attended a playground safety workshop at the 2006 National Association of School Nurses annual conference. Seventy-five questionnaires were distributed, and 64 useable questionnaires were returned. The responses indicated that little attention is being given to providing safe playground environments in schools as measured by best practices of supervision, age-appropriate desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In completing this systematic review, several studies were found that examined and reported on local and national compliance to playground standards. All of the studies found reported a significant lack of compliance (CDC, Centers for Disease Control and Prevention 1999;Acik et al 2004;Allen et al 2013;Chalmers et al 2001;Cradock et al 2010;Hudson et al 2008;Kotch et al 2003;Martin and Cooper 2005;Pickett et al 1996;Sherker and Ozanne-Smith 2004;Sherker et al 2009;Uskun et al 2008). For example, in the study by Pickett et al (1996), playgrounds in the Kingston, Ontario, area were investigated for adherence to CSA standards using a standardized checklist.…”
Section: Discussionmentioning
confidence: 99%
“…In completing this systematic review, several studies were found that examined and reported on local and national compliance to playground standards. All of the studies found reported a significant lack of compliance (CDC, Centers for Disease Control and Prevention 1999;Acik et al 2004;Allen et al 2013;Chalmers et al 2001;Cradock et al 2010;Hudson et al 2008;Kotch et al 2003;Martin and Cooper 2005;Pickett et al 1996;Sherker and Ozanne-Smith 2004;Sherker et al 2009;Uskun et al 2008). For example, in the study by Pickett et al (1996), playgrounds in the Kingston, Ontario, area were investigated for adherence to CSA standards using a standardized checklist.…”
Section: Discussionmentioning
confidence: 99%
“…Injury details: ________________________________________________________ Treatment given: _____________________________________________________ Suggestions: _________________________________________________________ School Principal/Nurse/Secretary _______________________________________ a crucial role in injury prevention. By recognizing the unsafe practices, school nurses can document and bring to attention the importance of safe playground behavior to administrators, staff, parents, and children (Hudson, Olsen, & Thompson, 2008). Prevention programs should be targeted largely toward elementary school students because there is an age relationship with respect to the likelihood of being injured at school (Josse et al, 2009).…”
Section: Implications For School Nursing Practicementioning
confidence: 99%
“…School nurses play a crucial role in injury prevention. By recognizing the unsafe practices, school nurses can document and bring to attention the importance of safe playground behavior to administrators, staff, parents, and children (Hudson, Olsen, & Thompson, 2008). Prevention programs should be targeted largely toward elementary school students because there is an age relationship with respect to the likelihood of being injured at school (Josse et al, 2009).…”
Section: Implications For School Nursing Practicementioning
confidence: 99%
“…The subject of supervision deserves attention because the lack of supervision is repeatedly mentioned as one of the biggest factors in playground injuries (Bruya, 1998; Frost & Sweeney, 1996; Hudson, Olsen, & Thompson, 2008; Thompson & Hudson, 2001). Specifically, school nurses have commented that there is not enough quality supervision, staff is minimally trained, and supervisors are standing in one place and talking to one another (Hudson et al, 2008).…”
Section: Developing a Playground Injury Prevention Planmentioning
confidence: 99%
“…School districts need to implement playground safety training for all staff members and children. Studies have shown that many schools do not conduct any type of training with the students (Bauer, 2001; Bruya, 1998; Bruya & Bruya, 2000; Hudson et al, 2008). Training is an intervention that helps everyone at the school to be consistent.…”
Section: Developing a Playground Injury Prevention Planmentioning
confidence: 99%